Limited Open Reduction and Internal Fixation of Calcaneal Fractures. (January 2020) - Bremer, Anne K.; Kraler, Lukas; Frauchiger, Lars; Krause, Fabian G.; Weber, Martin
Background: The treatment of displaced intra-articular calcaneal fractures remains a challenge and the optimal approach is still controversial. The main reason to avoid the extended lateral approach is the high complication rate due to wound healing problems. We report on 16 years of experience with a standardized limited open reduction and internal fixation technique. Methods: Between 2001 and 2017, we prospectively followed 240 consecutive patients operatively treated for a displaced intra-articular calcaneal fracture. Patients with open, multiple, bilateral, extra-articular, and Sanders IV fractures and those lost to follow-up were excluded. A lateral subtalar approach was used, with a cast for 8 weeks and full weightbearing allowed after 12 weeks. Follow-up examinations were scheduled until 24 months. Subjective and clinical assessment included gait abnormality, subtalar and ankle range of motion, and stability and alignment. The American Orthopaedic Foot & Ankle Society (AOFAS) hindfoot score was calculated. Alignment was analyzed on standard radiographs. In total, 131 patients were excluded. The remaining 109 patients were followed for a minimum of 24 months (34.4 ± 14.2 [range, 24-102] months). Results: The mean AOFAS score was 87 ± 13 (range, 32-100). "Excellent" and "good" results, as well as hindfoot motion with "normal/mild" and "moderate" restrictions, were seen in 80% of patients. Early reoperations were performed for insufficient reduction (2 patients), delayed wound healing (debridement, 3 patients), and hematoma (1 patient). Late revisions were arthrodesis (3 patients), medializing calcaneal osteotomy (1 patient), and implant removal (53 patients; 49%). Conclusion: The presented approach has remained unmodified for 16 years and resulted in consistently good functional results. The main disadvantage was the high rate of heel screw removal. Level of Evidence: Level IV, retrospective case series.